A Markov cost‐effective analysis of biannual fluoride varnish for preventing dental caries in permanent teeth over a 70‐year time horizon. (27th August 2019) - Nguyen, Tan Minh; Tonmukayakul, Utsana; Warren, Emma; Cartwright, Susan; Liew, Danny
Abstract: Issue addressed: Biannual application of fluoride varnish is effective for dental caries prevention, but its cost‐effectiveness using quality‐adjusted life years (QALY) is unknown. This study performed a cost‐effectiveness analysis, from the Australian health care system perspective of biannual application of fluoride varnish versus current practice (non‐routine application) for an individual aged 15 years and older over a 70‐year time horizon. Methods: Health outcomes measured were the number of prevented decayed, missing, and filled teeth (prevented‐DMFT) and QALY gained. The calculated incremental cost‐effectiveness ratio (ICER) was compared against the reference cost‐effectiveness ICER threshold of AUD$28 033 per QALY gained. A published Markov model capturing dental caries progression of eight permanent molars was used. This 6‐monthly cycle model represented ten possible health states for an individual tooth. A 5% discount rate was applied with relevant sensitivity analysis. Results: In the base‐case scenario, the net cost for the intervention was $3600 compared to $2303 in the current practice arm. The intervention arm yielded 13.99 DMFT and 15.44 QALY gained, whereas the current practice arm yielded 15.52 DMFT and 14.74 QALY gained. The estimated ICER was $849 per prevented‐DMFT and $1851 per QALY gained. Sensitivity analysis shows the ICER ranged from $424‐$1807 per prevented‐DMFT and $1851‐$3941 per QALY gained. Conclusion: Biannual professional application of fluoride varnish appears to be a highly cost‐effective strategy and should be considered for universal funding in Australia's health care system. Summary: Biannual application of fluoride varnish is efficacious at preventing dental caries among children, but its cost‐effectiveness in terms of health outcomes is unknown. This study performed a cost‐effectiveness analysis, from the perspective of the Australian health care system. The study demonstrated the intervention is likely to be highly cost‐effective.